Strategi pengembangan sumber daya manusia melalui pendidikan islam - Mauludya, Dita (Maliki Interdisciplinary Journal, 2025)
Strategies for developing Human Resources (HR) through Islamic Education with a qualitative approach to literature study. The results of the study show that Islamic education offers a holistic paradigm that views humans as abdullāh (servants of Allah) and khalīfah (leaders on earth). Islamic education serves as a transformative instrument through three approaches: at-ta'dīb (character building), at-ta'līm (transmission of knowledge), and at-tarbiyah (nurturing potential). From this framework, five operational strategies are identified: the integration of naqliyah and aqliyah knowledge; Exemplary-Based Learning (Qudwah Hasanah); the creation of an Islamic environment (bī'ah islāmiyyah); the development of 21st century prophetic competence and skills; and holistic evaluation. The implementation of these strategies aims to produce a superior and moral al-Insān al-Kāmil (perfect human being). Despite facing challenges such as curriculum dichotomy and educator quality gaps, there are strategic opportunities such as regulatory support and digital technology advancements. It is concluded that human resource development through Islamic education is a contextual and progressive civilization project.